Levels of hydrocarbons and toxicity of water-soluble fractions of maritime fuels on neotropical invertebrates - de Santana, Debora Cristina Nascimento [UNESP]; Perina, Fernando Cesar [UNESP]; Lourenço, Rafael André; da Silva, Josilene; Moreira, Lucas Buruaem [UNESP]; de Souza Abessa, Denis Moledo [UNESP] (My University, 2021)
Accidents involving fuels and oil spills are among the main sources of hydrocarbons to the marine ecosystems and often damage the biota. Diesel and bunker oil are two examples of fuels with broad application that release hydrocarbons to the aquatic environment and little is known about their toxicity on tropical organisms. This study aimed to assess the toxicity of the water-soluble fraction (WSF) of diesel and bunker oils to neotropical marine invertebrates. Commercial fuels were purchased for WSF extraction, analyzed for total petroleum hydrocarbons (TPH), and polycyclic aromatic hydrocarbons (PAHs), and acute and chronic toxicity determined. The WSF analyzed contained varied levels of TPH and PAHs mixtures, especially low molecular weight PAHs; bunker WSF presented higher amounts of TPH and PAHs. Both WSFs tested produced significant mortality of the brine shrimp Artemia salina, affected the reproduction rate of the copepod Nitokra sp, and impaired the embryo-larval development of the mussel Perna perna and of the sea urchin Lytechinus variegatus. In general WSF from diesel was more toxic to the organisms tested, but bunker WSF was more toxic to embryos of L. variegatus. Toxicity started from concentrations of 3% WSF, which can be environmentally relevant after an oil spill, indicating that marine biota may be adversely affected in short term.
Keywords: Marine ecotoxicology; Marine pollution; Oil spills; Polycyclic aromatic hydrocarbons; Species sensitivity; Total petroleum hydrocarbons